Reforestation in Southern China Enhances the Convective Afternoon Rainfall During the Post-flood Season - Li, Xing; Li, Xiao; Ma, Hedi; Hua, Wenjian; Chen, Haishan; Wen, Xiaohang; Zhang, Wanxin; Lu, Yiwen; Pang, Xueqi; Zhang, Xuanwen (Frontiers in Environmental Science, 2022)
Dynamic and continuous land use and cover change (LUCC) is one of the external forcing factors affecting regional climate in China. Based on the annual dynamic global land cover dataset derived from the Global Land Surface Satellite (GLASS-GLC), this paper modelled and investigated the effects of annual transient LUCC on precipitation over China using the regional climate model RegCM4.8.2. Analysis of the GLASS-GLC data revealed that considerable conversions of cropland to forest, grassland to cropland and bare ground to grassland had occurred during the last 3 decades (1984–2013) in southern, northeastern and northwestern China respectively. By comparing the differences between the two sets of experiments under the fixed LUCC and dynamic LUCC scenarios, the results showed that reforestation in southern China during the past 3 decades significantly enhanced local convective afternoon rainfall (CAR; ∼2 mm/day) during the post-flood season (POF; July-August-September). This reforestation effect on CAR also increased with the intensity of LUCC. However, the realistic LUCC effects were weak and negligible for other periods, regions and large-scale precipitation. Furthermore, we have identified two possible reasons that favored the occurrence of POFCAR, namely that the moisture and instability conditions required to trigger convections were both enhanced by reforestation. This was evidenced by increases (decreases) in convective available potential energy (lifting condensation level), increases in atmospheric water vapor content and declining tendencies of equivalent potential temperature with height. Overall, this study highlights the importance of reforestation impacts on the diurnal variations of the precipitation.